Performance testing through isokinetic strength and jump height measurements in Nordic Combined - Pyrka, P.; Veith, M.; Schüller, K.; Erlebeck, F.; Bösl, P.; Schwirtz, A. (World Congress of Performance Analysis of Sport VIII, 2008)
Our data confirms the well-known dilemma that concerns strength and speed strength development in Nordic combined. Athletes with higher BMI perform better on strength- and speed strength-related tests, whereas the sport, in particular the jumping competition, calls for a low weight with high explosive power. Our data also suggests that jump height is closely related to maximum relative isometric strength. This is in line with the common approach to buildmaximum strength at the beginning of the general preparation phase and then move over to explosive type of training in order to increase speed of motor unit recruitment. There is evidence that the eccentric-concentric ratio ekV exhibits a maximum during the summer and successively decreases towards the winter. This could be related to the common training concept that starts with maximizing strength of the available muscle mass (while at the same time avoiding muscle hypertrophy) in early summer and then turns to specific speed strength work-outs later on in the summer. However, questions concerning the underlying neuromuscular mechanisms with respect to ekV development remain. SJ jump heights - a highly specific test parameter - have improved over the summers in 2005-2007, which is most likely due to proper training methods and training compliance. However, future research should be directed towards confirming this hypothesis and / or find other parameters that have an influence on this development. More important, further studies should be concerned with relating laboratory test performance with competitive performance over the course of a world cup season. One has to be careful with the interpretation of our statistical analysis, mainly for two reasons. First, we have not investigated whether missing values (i.e. data not provided for some athletes at particular test days) are at random and do not have an effect on the levels of parameters evaluated. Second, the test design is not balanced. Some athletes provided for very few test parameters (less than five), while others provide data for more than 50. This could result in instability of parameter estimation. The case studies on three individuals from the German B-squad in 2006 suggest that despite overall development, responsiveness to specific training stimuli is highly individual and has to be closely monitored in order to optimize the preparation period. In addition, pre-test fatigue can have an effect on individual test results. Second, in order to evaluate training progress and the effectiveness of training contents and execution scientifically, suitable training variables have to be documented reliably by the athletes or coaching staff. It is one of our tasks to identify those variables and validate them in order to precisely evaluate effects of specific training programs on neuromuscular performance.